EFFICACY OF ENDOPHYTIC BACTERIA ON PLANT GROWTH PROMOTION AND BIOCONTROL OF Fusarium WILT IN TOMATO CROP - V. THULASI BAI (The Journal of Research ANGRAU, 2023)
Fusarium wilt is a serious disease in tomatoes leading to yield loss. In the study liquid formulations of two endophytic bacteria viz., Pseudomonas aeruginosa KM236234 (FR3) and Bacillus sp. KC817016 (FR19) were used for evaluating disease control potential and plant growth promotion (PGP) of tomato crops. Cell-free supernatants of both FR3 and FR19 could reduce the radial growth of Fusarium oxysporum (MTCC10270). FR3 and FR19 could also able solubilize phosphate and produce IAA at 28 °C and 37 °C. In this study, investigation was done on the effect of two plant growth-promoting (PGP) endophytic bacteria viz., Pseudomonas aeruginosa-FR3 and Bacillus sp.- FR19 when utilized alone, and in combination with each other on morphology and growth of tomato plants. Inoculation of endophytes significantly increased the plant growth parameters when compared to control. Plant biomass and root biomass 205,189,311%; 200,189,317% were increased in inoculated plants compared to non-treated control plants. The combined use of FR3 and FR19 had a positive impact on tomato morphological parameters and increased shoot biomass. P. aeruginosa (FR3) was found to have higher efficacy than Bacillus spp. (FR19) for plant growth and development, while the FR19 strain had higher antifungal activity than the FR3 strain.These results suggested that inoculation with Pseudomonas aeruginosa (FR3)and Bacillus sp (FR19) could be successfully used to enhance tomato biomass. A complete correlation was observed in plant growth parameters with inoculated FR3 and FR19-tested endophytic stains.